Makna Kesejahteraan Sosial Ekonomi Kelompok Difabel Masa Pandemi Covid 19 (IKIP PGRI Jember, 2023)
Persons with disabilities have equal rights, roles and opportunities in society. The physical and mental limitations experienced by persons with disabilities do not make them despair. Just like other individuals, people with disabilities also want to get socio-economic welfare. In addition to their shortcomings, people with disabilities also have advantages in the form of potential that can be developed. This potential can be used as a tool to achieve socio-economic welfare. The research method used is qualitative with a socioethnographic approach. Data analysis used the Miles & Huberman socioethnographic triangulation model. Data analysis activities include data collection, data reduction, data presentation, and conclusions. Based on the results of interviews conducted with the Difabel group in Turi Rejo Village, it is known that getting recognition and appreciation as well as equal education from the community is one of the meanings of social welfare that is expected to be obtained by the Difabel group. In addition, the Difabel group also explained that they also practice to work to develop their talents and interests in entrepreneurship. Based on these data, it was concluded that the meaning of social welfare for the disabled group in Turi Rejo Village, Malang Regency during the Covid 19 pandemic, received recognition and appreciation as well as equal education from the community. Meanwhile, the economic meaning for the disabled group in Turi Rejo Village, Malang Regency is getting the opportunity to work and work so that economic needs can be met.